Barn owl productivity responses to fluctuating vole populations - Pavluvčík, P.; Poprach, K.; Machar, I.; Losík, J.; Gouveia, A.; Tkadlec, E. (Emil) (2015)
Recently ecologists have recognized the importance of environmental variability on population growth rate and individual fitness. Vole population dynamics is typical pulse resource with long intervals of low abundance and short intervals of superabundance. There is sufficient evidence that the productivity of vole-eating predators follows closely changes in vole\ndensities. However, we are less informed about the responses of predators to changing variability of food resource availability. We studied the system barn owl–common vole to examine the variation in barn owl (Tyto alba) annual productivity dependent on common vole (Microtus arvalis) fluctuating numbers. Between 1998 and 2013, 681 active nesting sites situated in 17 Czech districts were examined every year. In each examined district, vole abundances were measured using a burrow index, the number of active burrow entrances per hectare. The description of the functional relationship at the level of the Czech Republic\nrevealed that owl abundance covaried more with autumn than spring vole abundances. The relationship was linear. By focusing on the variation in annual productivity at the district level relative to the vole population variability, we found that the responses in annual productivity were indeed stronger in districts with higher population variability of voles.